Effectiveness and safety of chronic hepatitis C treatment with direct-acting antivirals in patients with rheumatic diseases: A case-series. Issue 6 (1st November 2020) - Kida, Takashi; Umemura, Atsushi; Kaneshita, Shunya; Sagawa, Risa; Inoue, Takuya; Toyama, Shogo; Wada, Makoto; Kohno, Masataka; Oda, Ryo; Inaba, Tohru; Itoh, Yoshito; Kawahito, Yutaka
Abstract: Objectives: To assess the effectiveness and safety of interferon-free direct-acting antiviral (DAA) therapy for patients with concomitant hepatitis C virus (HCV) infection and rheumatic diseases (RDs), including rheumatoid arthritis (RA). Methods: This was a single-center observational case-series study conducted in Japan from 2014 to 2018. The primary endpoint was the sustained virological response (SVR) rate 24 weeks after the end of therapy (EoT24). We also evaluated hepatological and rheumatological outcomes and adverse events. Results: Of the 2314 patients with RDs, 18 received DAA therapy (RA = 11, other RDs = 7). The SVR rate for the initial DAA therapy was 89% (16/18). The remaining two achieved SVR with secondary DAA therapy. Along with HCV elimination, hepatological parameters improved significantly from baseline to EoT24. During the study period, no patients newly developed cirrhosis or HCC after HCV elimination. Several patients showed improvement in RDs activity. In RA patients, the simplified disease activity index decreased significantly from baseline to EoT24 (median [interquartile range]: 11.53 [5.14–14.89] vs. 4.06 [2.08–9.05], respectively). On-treatment adverse events were minimal, while two patients experienced tuberculosis reactivation after EoT. Conclusion: DAA therapy was effective and safe, providing hepatological and rheumatological benefits in HCV-infected patients with RDs. Immune reconstitution following HCV elimination should be noted.